2020
DOI: 10.1371/journal.pone.0237362
|View full text |Cite
|
Sign up to set email alerts
|

Association of the long fluoroscopy time with factors in contemporary primary percutaneous coronary interventions

Abstract: Background Since the long fluoroscopy time in primary PCI for ST-segment elevation myocardial infarction (STEMI) could be an indicator of delayed reperfusion, it should be important to recognize which types of lesions require longer fluoroscopy-time in primary PCI. The purpose of this study was to investigate the association of the long fluoroscopy-time with clinical factors in primary percutaneous coronary interventions (PCI). Methods A total of 539 patients who underwent primary PCI were divided into the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In this study, a univariate analysis showed that three-coronary vessel disease, not highly experienced operators, and a pre-TIMI flow grade 3 were more likely to be associated with a long sheath insertion to the first balloon time; however, it was not evident for the potential factors such as diabetes, the lesion length, severe calcifications, etc., which were derived from the data to explore the associated factors of the long fluoroscopy time [ 29 ] via mixed approaches including the radial artery, femoral artery, or rarely, the brachial artery. Although the exact explanation of those 3 associated factors was unclear, three-coronary vessel disease and a pre-TIMI flow grade 3 may be confounders of severe coronary disease and/or severe tortuosity, and a pre-TIMI flow grade 3 may be an inverse consequence of physicians having hurriedly performed the revascularization in patients who had a pre-TIMI follow grade of ≤2.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a univariate analysis showed that three-coronary vessel disease, not highly experienced operators, and a pre-TIMI flow grade 3 were more likely to be associated with a long sheath insertion to the first balloon time; however, it was not evident for the potential factors such as diabetes, the lesion length, severe calcifications, etc., which were derived from the data to explore the associated factors of the long fluoroscopy time [ 29 ] via mixed approaches including the radial artery, femoral artery, or rarely, the brachial artery. Although the exact explanation of those 3 associated factors was unclear, three-coronary vessel disease and a pre-TIMI flow grade 3 may be confounders of severe coronary disease and/or severe tortuosity, and a pre-TIMI flow grade 3 may be an inverse consequence of physicians having hurriedly performed the revascularization in patients who had a pre-TIMI follow grade of ≤2.…”
Section: Discussionmentioning
confidence: 99%
“…From the last few decades, a growing number of patients have undergone PCI through radial artery route with increasing cases in which direct PCI and interventional PCI were carried out. A previous study reported that PCIs were performed through the right radial and left radial artery in 89.4% and 10.6% respectively [11]. Another study found that the majority of physicians have chosen a radially artery route for performing PCI on a routine basis [12].…”
Section: Discussionmentioning
confidence: 99%
“…We should also discuss why moderate-severe calcification was associated with the difficulty in crossing the culprit lesion. Although there were few reports showing that calcification was the factor of difficulty in crossing the culprit lesion of AMI, it is widely known that calcification is associated with the difficulty of PCI 21 . Severe calcification causes unsuccessful device delivery, stent under-expansion, and long-term stent failure 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In an original ACC/AHA definition, tortuosity was defined as follows: stenoses distal to two bends were defined as moderately tortuous, and those distal to three or more bends were defined as excessive tortuosity 20 . However, since the above definition of tortuosity has poor objectivity, we additionally defined tortuosity as follows: “ ≤ 1” moderate to excessive bend (< 120°) was defined as mild tortuosity, “2” moderate to excessive bend (< 120°) was defined as moderate tortuosity, and “ ≥ 3” moderate to excessive bend (< 120°) was defined as excessive tortuosity 21 . Calcification was identified as readily apparent radiopacities within the vascular wall at the site of the stenosis, and was classified as none/mild, moderate (radiopacities noted only during the cardiac cycle before contrast injection), and severe (radiopacities noted without cardiac motion before contrast injection generally compromising both sides of the arterial lumen) 22 .…”
Section: Methodsmentioning
confidence: 99%